Second Five-Year Plan Programme for 1959-60 Mysore State - Planning Commission (Planning Commission, 1989)
Strenuous efforts are being made to accelerate the progress so that the State may make up in two years, for the deficiencies of the first three years of the Plan. Various measures to speed up administrative sanctions, delegation and decentralization of powers, detailed reviews periodically to locate difficulties and action to eliminate them, will, it is hoped, improve the pace of progress. Development schemes amounting to about Rs. 3 crores which were outside the Plan till now, have been included in the Plan for 1959-60.
Government of Mysore